Influence Of Marketing Mix And Customer Relationship Management On Customer Loyalty In Pt. Abc In Jakarta - Sari, Ovi Hamidah (Universitas Tarumanagara, 2017)
The purpose of this study is to investigate influence of service marketing mix and customer relationship management to customer loyalty at pt. abc. the problem in this study was formulated in the 2 hypothese were tested by using spss version 19 with 150 respondents. . This is a descriptive research that using a questionnaire to collect the data. The non-probabilistic sampling method is used in this research. The data analysis technique is a multiple regression analysis. . The results showed that service marketing mix and customer relationship management positively affect customer loyalty.